Evolution of the Santana do Araguaia (PA) region based on geology and Pb-Pb zircon geochronology from granitoid rocks - Corrêa, Lívio Wagner Chaves; Macambira, Moacir José Buenano (Geologia USP. Série Científica, 2014)
The region of Santana do Araguaia, focus of this study, is located in the southeast of Pará State, which, in its turn, lies in the southeastern Amazonian Craton. From the tectonic point of view, it is positioned in the Domain Santana do Araguaia, interpreted as an Archean terrain affected by the Transamazonic Cycle. A petrographic and geochronological study, supported by field data, was undertaken in granitoids of the region in order to unravel the evolution of this field. In modal terms, the studied rocks consist of biotite monzogranite, biotite metagranodiorite, hornblende-biotite granodiorite, hornblende-biotite metatonalite and enderbite. These rocks present themselves undeformed to moderately deformed, with some particularities: the biotite metagranodiorite presents foliation following an E-W trend; the hornblende-biotite metatonalite has a foliation following the NW-SE direction, usually with high to subvertical dives, the biotite monzogranite is isotropic, and lithologies hornblende-biotite granodiorite and enderbite show only a slight orientation of their crystals, mainly noticeable in thin section. These rock types were analyzed by evaporating Pb zircon method and the following ages were obtained: biotite metagranodiorite, 3066 ± 3 Ma and 2829 ± 13 Ma, hornblende-biotite metatonalite, 2852 ± 2 Ma, biotite monzogranite, 2678 to 2342 Ma, hornblende-biotite granodiorite, 1990 ± 7 Ma, and enderbite, 1988 ± 4 Ma. The geochronological data indicate that the rocks crystallized both in the Archean and in the Paleoproterozoic; however, no evidence to prove the action of the Transamazonic Cycle was detected in the region.